SOFT POWER DAN KOMPETISI EKONOMI KREATIF DI ASIA TENGGARA: STUDI KASUS THE ERAS TOURS TAYLOR SWIFT 2024 - Umul Fadilatul Ulla; Kayla Azalia Syafila; Fahmy Aditya Wibisana (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The = The phenomenon of Taylor Swift’s The Eras Tour 2024 concert in Singapore illustrates how the global entertainment industry has become an important instrument in cultural diplomacy and the creative economy. This study aims to analyze how soft power and competition within the creative economy operate in the Southeast Asian context through a case study of the exclusivity of Taylor Swift’s concert in Singapore. Using a descriptive qualitative method based on a literature review, this research examines the interrelation between soft power strategies, the creative economy, and the dynamics of ASEAN regionalism. The findings indicate that Singapore leveraged the concert as a soft power strategy to strengthen its national image as a cultural and creative economy hub in the region, while simultaneously attracting investment and boosting the tourism and entertainment sectors. However, the decision to grant concert exclusivity generated diplomatic tensions and rivalry among ASEAN countries such as Thailand and the Philippines, which perceived themselves as having lost potential economic and cultural opportunities. This phenomenon underscores that soft power has become a new arena of competition in Southeast Asia, where the creative economy functions not only as a driver of economic growth but also as a political instrument influencing regional solidarity and relations within the ASEAN cooperation framework.